HYDRAULIC TIRE PRESS - SINGH, ANAND PAL; SHICHMAN, DANIEL (1988)
A dual cavity hydraulic tire press utilizes a single long stroke piston-cylinder assembly vertically positioned substantially in line with the center of gravity of the vertically movable upper mold sections, the latter being supported on the underside of the outer ends of a shallow V-shaped beam which is mounted for vertical movement on a readily removable column or post. In the closed position of the press the top mold cavities are locked to the base of the press by rotatable bayonet locks. Four short stroke hydraulic clamp piston-cylinder assemblies are positioned beneath each bottom mold section to achieve clamping pressure during cure. In one embodiment mechanical stops may be provided to achieve mold height adjustment and to preclude the molds opening significantly upon loss of fluid pressure to the clamping piston-cylinder assemblies. In another embodiment the clamp-piston-cylinder assemblies are mechanically adjusted to obtain the proper position for mold height adjustment. The press includes a safety bar which is supported from the top mold section for part of its movement with the bar being held stationary during initial opening movement of the top molds, and then picked up to be in a position just below extended segment molds if employed. The clamp-piston-cylinder assemblies are provided with extended coolant passages between the clamp actuating fluid and the heat of the mold cavity to preclude degradation of the fluid employed. The isolation of the clamp pressure at four equally spaced points beneath the bottom platen enables the platens and molds to be more efficiently encased with insulating materials not subject to high pressure during cure. The position of the clamp-piston-cylinder assemblies as well as the piston-cylinder assembly opening and closing the press preclude hydraulic fluid contamination of the uncured or cured tires passing through the press. With the present invention, a tire curing press of substantially less weight, envelope and energy consumption can be provided.